2013
DOI: 10.1101/sqb.2013.78.020321
|View full text |Cite
|
Sign up to set email alerts
|

The IRF Family Transcription Factors at the Interface of Innate and Adaptive Immune Responses

Abstract: The interferon-regulatory factor (IRF) family, originally identified as transcriptional regulators of the type I interferon system, consists of nine members in mammals. A large number of studies have revealed the versatile and critical functions performed by this transcription factor family in immunity and other biological processes. Most notably, the advances in the study of signal transducing innate immune receptors have placed many IRF members as central mediators in the regulation of innate immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
172
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(182 citation statements)
references
References 117 publications
8
172
1
1
Order By: Relevance
“…Although IRF1 is known to be strongly induced in macrophages by IFN-g, the detailed functional role and the mecha- nisms of IRF1 in regulating immune responses are poorly understood (19). IRF1 plays a major role in the transcriptional regulation of Il12a but not Il12b (20), although an IRF1-binding element was characterized in the Il12b promoter (21).…”
Section: Discussionmentioning
confidence: 99%
“…Although IRF1 is known to be strongly induced in macrophages by IFN-g, the detailed functional role and the mecha- nisms of IRF1 in regulating immune responses are poorly understood (19). IRF1 plays a major role in the transcriptional regulation of Il12a but not Il12b (20), although an IRF1-binding element was characterized in the Il12b promoter (21).…”
Section: Discussionmentioning
confidence: 99%
“…51 Substantial previous studies indicated that TLRs recognize pathogen-associated molecular patterns derived from various microbes in response to infections. 184,185 Apart from the exogenous molecules, TLR ligands have been found including a much broader range of endogenous components, eg, lipopolysaccharide, HMGB1, danger-associated molecular patterns, heat shock proteins, and lipopeptides, which are released from injured/ inflamed tissues and dying cells.…”
Section: Upstream Irf Signaling In Obesity Insulin Resistance and Hmentioning
confidence: 99%
“…A large number of studies have revealed the versatile and critical functions performed by IRF family in innate immunity [5658], adaptive immunity [57] and many other biological processes, such as immune cell development [56,58], regulation of gene expression in response to pathogen infection [56,59,60],regulation of the cell cycle [61,62] and apoptosis [63,64]. The MAF is a family of transcription factor protein that belongs to the activated protein-1 super-family of transcription factors.…”
Section: Discussionmentioning
confidence: 99%